2009
DOI: 10.1519/jsc.0b013e31819bbea4
|View full text |Cite
|
Sign up to set email alerts
|

Hip and Knee Extensor Moments Predict Vertical Jump Height in Adolescent Girls

Abstract: Biomechanical factors, such as hip and knee extensor moments, related to drop jump (DJ) performance have not been investigated in adolescent girls. The purpose of this study was to determine the key independent biomechanical variables that predict overall vertical jump performance in adolescent girls. Sixteen high school adolescent girls from club–sponsored and high school–sponsored volleyball teams performed DJ at 3 different drop heights (15, 30, and 45 cm). A motion analysis system consisting of 10 digital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Sport-specialized athletes also experienced a smaller increase in knee extensor moment during landing. While over-reliance on the knee extensors during landing can be an indicator of decreased hip control and subsequent lower extremity injury risk (43), it can also indicate improved task performance, particularly during the DVJ (44). For the multi-sport group, these results (i.e., greater increase in knee extensor moment, smaller increase in knee abduction moment, and trend toward a greater increase in hip extensor moment (Figure 2) indicate that multi-sport athletes tend to exhibit more improved landing performance during the DVJ.…”
Section: Discussionmentioning
confidence: 99%
“…Sport-specialized athletes also experienced a smaller increase in knee extensor moment during landing. While over-reliance on the knee extensors during landing can be an indicator of decreased hip control and subsequent lower extremity injury risk (43), it can also indicate improved task performance, particularly during the DVJ (44). For the multi-sport group, these results (i.e., greater increase in knee extensor moment, smaller increase in knee abduction moment, and trend toward a greater increase in hip extensor moment (Figure 2) indicate that multi-sport athletes tend to exhibit more improved landing performance during the DVJ.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the DJ, the prestretch augmentation from various drop heights has been minimally investigated in children. Only one study reported that pubertal female basketball players have no gain in jumping when dropping from 15 to 45 cm, nonetheless, these results were not compared with their performance in SJ (13). On this issue, a recent study suggested that the superiority of men in 20 cm DJ compared with boys could be attributed to a more optimal stiffness regulation of the muscle-tendon unit (29).…”
mentioning
confidence: 99%
“…One study concluded hip extension endurance is significantly correlated to patellofemoral pain and altered kinematics during running (Souza & Powers, 2009). Another study demonstrated that hip extension power is linked to vertical jump height (Ford et al, 2009). Evidence suggests gluteal power and endurance are significant facets of function separate from gluteal strength.…”
Section: Introductionmentioning
confidence: 99%